Ozone treatment as a disinfectant of commercial eggs to preserve function quality - PARVIN, P AHANGAR; ZAKERI, A; HIDARNEJAD, K; MOGHADDASZADEH-AHRABI, S (The Indian Journal of Animal Sciences, 2020)
Ozone is a strong oxidant used for the disinfection of surfaces, drinking water and foods. However, since ozone not only destroys bacteria but may also damage eggs, it is necessary to clarify the effects of ozone treatment on commercial egg components. In this study, different doses of ozone gas, 2, 4, 6 and 10 ppm were used. Salmonella entritidis infected eggs were dosed in different experimental groups at different doses of ozone for 15 min. Factors such as TBC, Salmonella entritidis, pH of egg contents, shell hardness, peroxide content in egg contents and albumen viscosity were measured after 10 days of application. The best amount of ozone gas was obtained at concentrations of 6 and 10 ppm for disinfection of different parts of the egg. While the amount of peroxide produced at 10 ppm was more than standard and harmful. Generally, the application of ozone gas at doses of 4 ppm, especially at 6 ppm, showed the best results for the measured factors. The use of gas at 6 ppm for 15 min can be used to keep the eggs fresh with maximum disinfection. This can be done in the egg industry, in order to remove Salmonella entritidis and maintain the quality of commercial eggs.